Sphaerococcus coronopifolius bromoterpenes as potential cancer stem cell-targeting agents - Alves, Celso (2020)
Cancer is one of the major threats to human health and, due to distinct factors, it is expected that its incidence will increase in the next decades leading to an urgent need of new anticancer drugs development. Ongoing experimental and clinical observations propose that cancer cells with stem-like properties (CSCs) are involved on the development of lung cancer chemoresistance. As tumour growth and metastasis can be controlled by tumourassociated stromal cells, the main goal of this study was to access the antitumor potential of five bromoterpenes isolated from Sphaerococcus coronopifolius red alga to target CSCs originated in a co-culture system of fibroblast and lung malignant cells. Cytotoxicity of compounds (10–500 μM; 72 h) was evaluated on monocultures of several malignant and non-malignant cells lines (HBF, BEAS-2B, RenG2, SC-DRenG2) and the effects estimated by MTT assay. Co-cultures of non-malignant human bronchial fibroblasts (HBF) and malignant human bronchial epithelial cells (RenG2) were implemented and the compounds ability to selectively kill CSCs was evaluated by sphere forming assay. The interleucine-6 (IL-6) levels were also determined as cytokine is crucial for CSCs. Regarding the monocultures results bromosphaerol selectively eliminated the malignant cells. Both 12S-hydroxy-bromosphaerol and 12R-hydroxy-bromosphaerol steroisomers were cytotoxic towards non-malignant bronchial BEAS-2B cell line, IC50 of 4.29 and 4.30 μM respectively. However, none of the steroisomers induced damage in the HBFs. As to the co-cultures, 12R-hydroxy-bromosphaerol revealed the highest cytotoxicity and ability to abrogate the malignant stem cells; however its effects were IL-6 independent. The results presented here are the first evidence of the potential of these bromoterpenes to abrogate CSCs opening new research opportunities. The 12R-hydroxy-bromosphaerol revealed to be the most promising compound to be test in more complex living models.